Mental health: outcomes of 10 babies of mothers with a history of serious mental illness. Issue 7 (8th October 2013) - McCauley, K. M.; Cross, W.; Kulkarni, J.
Accessible summary Women with serious mental illness are frequently on antipsychotic medications to maintain their mental health (MI). Antipsychotic medications are currently not approved for use in pregnancy because of the lack of evidence about their risk of harming the baby. These include kidney malformations, limb malformation and congenital heart disease. This case study series identifies the outcomes for 10 babies of women with serious MI. Gestation of the 10 babies at birth ranged between 29 and 40 weeks, average weight 2.9 kg. Two babies were born preterm. This study identifies the neonatal complications for these vulnerable babies as not outside the norm for births in Australia. There was however a high rate of mother–baby separation (4/10) which is of great concern. Abstract Women with serious mental illness are frequently on antipsychotic medications to maintain their mental health. During pregnancy there is much debate as to whether to continue or cease these medications. The possibility of adverse effects is of concern to clinicians and the women. This study used a case study methodology to identify the outcomes for 10 babies of women with a history of serious mental illness. The results provide further evidence in regard to women and the use of antipsychotic medications throughout pregnancy and during the first year after birth. Separation of mother and baby occurred in five of the 10 babies. This study identifies the neonatal complications for these vulnerable babies as not outside the norm for births in Australia. The high rate of mother–baby separation is of great concern and needs further longitudinal studies.